2013
DOI: 10.17269/cjph.104.3803
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Difficulties and Exclusivity Among Late Preterm and Term Infants: Results From the All Our Babies Study

Abstract: reterm birth is defined as delivery of a live born infant before 37 weeks of completed gestation. 1 Worldwide, about 15 million babies (more than 10% of all births) are born preterm. 1 There are three commonly used or established categories of preterm birth based on gestational age: very early (<32 weeks), early (32 0/7 -33 6/7 weeks), and late preterm (LP; 34 0/7 -36 6/7 weeks). "Late preterm" was introduced to replace the "near term" descriptor to differentiate this group as more similar to preterm infants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…In regards to duration, these researchers also found that mothers of LPIs were more likely to discontinue breastfeeding by 4‐months postpartum. The risk of early breastfeeding cessation in the late preterm population was also supported by Nagulesapillai et al () who found that LPIs are at increased risk of exclusive breastfeeding cessation by 4‐months postpartum compared to term infants. Mothers identified the most significant breastfeeding difficulties related to infant issues, such as a sleepy infant.…”
Section: Resultsmentioning
confidence: 68%
“…In regards to duration, these researchers also found that mothers of LPIs were more likely to discontinue breastfeeding by 4‐months postpartum. The risk of early breastfeeding cessation in the late preterm population was also supported by Nagulesapillai et al () who found that LPIs are at increased risk of exclusive breastfeeding cessation by 4‐months postpartum compared to term infants. Mothers identified the most significant breastfeeding difficulties related to infant issues, such as a sleepy infant.…”
Section: Resultsmentioning
confidence: 68%
“…The rates of exclusive or predominant breastfeeding were lower in this study than in WHO MGRS (MGRS -approximately 80 and 63 %; PPFS -65.3 and 56.5 % at 4 weeks and 3 months, respectively) [19]. These results are not unexpected as breastfeeding rates are generally lower in preterm compared to term infants [9,[20][21][22], and establishing and maintaining breastfeeding in preterms requires considerable support. Factors that may impact upon the ability of preterms to breastfeed are clinical conditions related to prematurity, extended hospitalization, increased sleepiness and maternal illness.…”
Section: Discussionmentioning
confidence: 65%
“…Nagulesapillai and colleagues found that 55% of mothers of LPIs exclusively breastfed at 4 months in Calgary [12]. The discrepancies may be attributed to the fact that the difficulties encountered during the early breastfeeding experience may have been overcome by the time the LPIs were 4 months of age.…”
Section: Discussionmentioning
confidence: 99%